Uncertainty and Monetary Policy in Good and Bad Times - Giovanni Caggiano; Efrem Castelnuovo; Gabriela Nodari (Center for Economic Studies and ifo Institute (CESifo), 2017)
We investigate the role played by systematic monetary policy in tackling the real effects of uncertainty shocks in U.S. recessions and expansions. We model key indicators of the business cycle with a nonlinear VAR that allows for different dynamics in busts and booms. Uncertainty shocks are identified by focusing on historical events that are associated to jumps in financial volatility. Uncertainty shocks hitting in recessions are found to trigger a more abrupt drop and a faster recovery in real activity than in expansions. Counterfactual simulations suggest that the effectiveness of systematic monetary policy in stabilizing real activity is greater in expansions. Finally, we provide empirical and narrative evidence pointing to a risk management approach by the Federal Reserve.
Keywords: C32; E32; 330; uncertainty shocks; nonlinear Smooth Transition Vector AutoRegressions; Generalized Impulse Response Functions; systematic monetary policy